Clinical and Pathological Studies on Cattle Experimentally Infected with Theileria annulata in China - Ma, Quanying (Pathogens, 2020)
Theileriosis is an important tick-borne protozoosis that causes high morbidity and mortality in cattle. In this study, the pathological and clinical characteristics of cattle experimentally infected with Theileria annulata were investigated. The clinical findings revealed typical signs of bovine theileriosis, including fever, enlargement of superficial lymph nodes, anemia, and respiratory distress. The most common pathological features were petechial and ecchymotic hemorrhages on the mucosa and serosal surface, severe jaundice, pulmonary edema and emphysema, multifocal necrosis and numerous ulcerations in the abomasum, congestion and marble-like discoloration of the spleen, and severe intestinal ecchymotic hemorrhages. The main histological characteristics were proliferation and infiltration of lymphocytes, plasma cells, and macrophages in the lymph nodes, spleen, and lymph node mass. Macroschizonts were observed in the cytoplasm of lymphocytes and macrophages of the lymph nodes and spleen. This study has significance for basic research and the clinical detection and diagnosis of Theileria annulata infection and can aid the prevention and control of theileriosis and future studies of the pathogenic mechanisms.